Tingkat Ketakutan (Fear of COVID Scale) Masyarakat di Masa Pandemi COVID-19 - Hoirunnisa, Hoirunnisa; Arwan, Artiarini Puspita (Jurnal Penyuluhan Agama, 2022)
Abstract: The Covid-19 pandemic has an impact on a person's psychology and even the wider community, such as feelings of fear, worry, depression, stress and anxiety. This study aims to determine the level of public fear in the face of the Covid-19 pandemic. This study uses a quantitative research design with a cross sectional approach. The population in this study was the age group of 14-60 years from adolescence to late adulthood. Based on gender, the sample consisted of 209 males and 266 females with a total of 475 respondents. The sampling technique used was non-probability sampling, namely accidental sampling. Data collection uses google forms which are shared through various social media. The research instrument used was the Fear of covid -19scale (FCV-19S) developed by Ahorsu, et. All (2020) which consists of 7 items. In this study, 14 items were added, with a total of 21 items. The independent variables of this study were gender and age. The variable of this research is the level of people's fear. Statistical test used for univariate analysis is frequency distribution and bivariate analysis using chi-square test. Tests used in this study using Amos and SPSS software. The results of the community network level for Covid-19 based on gender are at a moderate level of fear, with a higher percentage of women, namely 57% and men 43%. The results of the Covid-19 network relationship test with gender were said to be significantly related to a chi-square value of 0.001 (< 0.05). Likewise, the results of the community's level of fear of Covid-19 based on age are at a moderate level of fear, with the percentage of adults being 90% higher than 10% of teenagers. The results of the test of the relationship between COVID-19 fear and age were said to be not significantly related, because the chi-square value was >0.05 (0.265).Abstrak: Pandemi Covid-19 khawatir berdampak pada psikologis seseorang bahkan masyarakat luas, seperti perasaan takut, khawatir, tertekan, stress dan kecemasan. Penelitian ini bertujuan mengetahui tingkat ketakutan masyarakat dalam menghadapi pandemi Covid-19. Penelitian ini menggunakan desain penelitian kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah usia 14-60 tahun kategori remaja sampai dewasa akhir. Berdasarkan jenis kelamin, sampel terdiri atas 209 laki-laki dan 266 perempuan dengan total 475 responden. Teknik pengambilan sampel menggunakan non probabillity sampling yaitu accidental sampling. Pengumpulan data menggunakan google form yang dibagikan melalui berbagai media sosial. Instrumen penelitian yang digunakan adalah Fear of covid -19scale (FCV-19S) yang dikembangkan oleh Ahorsu, et. All (2020) yang terdiri dari 7 item. Pada penelitian ini ditambahkan 14 item, dengan jumlah keseluruhan 21 item. Variabel bebas penelitian ini adalah jenis kelamin dan usia. Variabel terikat penelitian ini adalah tingkat ketakutan Covid-19 masyarakat. Uji statistik yang digunakan untuk analisis univariat adalah distribusi frekuensi serta analisis bivariat menggunakan uji chi-square. Pengujian yang digunakan dalam penelitian ini menggunakan software Amos dan SPSS. Hasil tingkat ketakutan masyarakat terhadap Covid-19 berdasarkan jenis kelamin berada pada tingkat ketakutan sedang, dengan presentase perempuan lebih banyak yaitu 57% dan laki-laki 43%. Hasil uji hubungan ketakutan Covid-19 dengan jenis kelamin dikatakan berhubungan signifikan dengan nilai chi-square 0,001 (<0,05). Begitupun dengan hasil tingkat ketakutan masyarakat terhadap Covid-19 berdasarkan usia berada pada tingkat ketakutan sedang, dengan presentase usia dewasa jauh lebih banyak 90% dibandingkan usia remaja 10%. Hasil uji hubungan ketakutan covid-19 dengan usia dikatakan tidak berhubungan signifikan, karena nilai chi-square >0,05 (0,265).